2016
DOI: 10.4103/0366-6999.194661
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Prognostic Value of International Prognostic Score in Chinese Advanced Hodgkin Lymphoma Patients Treated in the Contemporary Era

Abstract: Background:The International Prognostic Score (IPS) was developed based on the data of Western advanced Hodgkin lymphoma (HL) patients treated before 1992. Only a few studies ever evaluated the application value of IPS in Chinese population or in patients treated in the contemporary era whose outcomes has improved significantly than before.Methods:We conducted a retrospective study involving 208 previously untreated Chinese advanced HL patients, who were admitted to Cancer Hospital Chinese Academy of Medical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…But these studies including a small group of patients and didn't analyze cHL alone. Some other studies also found anemia [22], eosinophilia [23], elevated β2-microglubin [19] and elevated serum ferritin [24] to be adverse factors. Thus, our study analyzed all the factors above that could be collected, and then included factor with p-value < 0.100 into multivariate analysis.…”
Section: Discussionmentioning
confidence: 92%
“…But these studies including a small group of patients and didn't analyze cHL alone. Some other studies also found anemia [22], eosinophilia [23], elevated β2-microglubin [19] and elevated serum ferritin [24] to be adverse factors. Thus, our study analyzed all the factors above that could be collected, and then included factor with p-value < 0.100 into multivariate analysis.…”
Section: Discussionmentioning
confidence: 92%
“…However, the data from two Chinese cohorts did not reveal a comparable conclusion, where younger patients with HL did not necessarily have better FFP than elderly patients. 10 , 21 Diverse age distribution among different study cohorts could be one explanation for this data discrepancy. Approximately 20% of patients were aged ≥60 years in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…This could explain our results, which were further validated by other analyses, showing that stage IV was related to worse FFP and OS. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For IPS: we could not study the best cut-off point suitable for our patients because the pilot study data did not include Albumin analysis results. Therefore, we relied on what is found in the medical literature, we considered that IPS of 3 represent the best cut-off point [9,10].…”
Section: Examination and Analysesmentioning
confidence: 99%